Material driven design for a chocolate pavilion. (April 2015) - Jordan, Alexander; Adriaenssens, Sigrid; Kilian, Axel; Adriaenssens, Mark; Freed, Zachary
Abstract: This paper presents a study of chocolate's structurally unusual material properties and a parametric design-to-construction approach for an architectural chocolate pavilion. Chocolate's rheological properties suggested exploration of four structural typologies: a pneumatic form, an inverted branching form, a saddle form, and an inverted hanging cloth form. Material tests revealed a compressive strength/weight ratio 24 times smaller than standard concrete. To use unreinforced chocolate, this restriction dictated a form with minimal bending: an inverted hanging shell with voids. An integrated form-finding, void-optimization and mold layout process was employed to minimize self-weight. Pre-casting planar pieces allowed for best control of material quality but added further design constraints. Prototypes demonstrated how the parametric workflow allows design exploration driven by adjustable material constraints, further integrating design and construction into an interdependent process. Highlights: Determination of structural properties of compound chocolate. Physical exploration of material appropriate structural systems for chocolate. Parametrically integrated design-to-construction process for free-form chocolate shell structures. Integration of material specific structural, manufacturing, and construction constraints into the design process.